2015
DOI: 10.5751/es-07519-200238
|View full text |Cite
|
Sign up to set email alerts
|

An alternative policy evaluation of the British Columbia carbon tax: broadening the application of Elinor Ostrom’s design principles for managing common-pool resources

Abstract: ABSTRACT. Climate change is putting infrastructure, food supply, water resources, ecosystems, and human health at risk. These risks will be exacerbated depending on the degree of additional greenhouse gas emissions. Urgent action is needed to limit the severity of impacts associated with further warming. British Columbia (BC) has taken action to reduce greenhouse gas emissions from carbonbased fuels by introducing a carbon tax in 2008. As an innovative approach to climate change mitigation, especially in North… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…Tyson (2017) similarly used the SES framework to illustrate the advantages and limitations a large comanagement effort, the Inuvialuit Settlement Region in northern Canada. Lacroix and Richards (2015) applied the design principles to the carbon tax in British Columbia, Canada, and found that their assessment added insights beyond those provided by existing policy analyses. Ban et al (2015b) used a SES lens to examine changes in governance through time in the Great Barrier Reef Marine Park, Australia, assessing changes in property rights and multiple goods and ecosystems services.…”
Section: Summary Of the Articlesmentioning
confidence: 99%
See 2 more Smart Citations
“…Tyson (2017) similarly used the SES framework to illustrate the advantages and limitations a large comanagement effort, the Inuvialuit Settlement Region in northern Canada. Lacroix and Richards (2015) applied the design principles to the carbon tax in British Columbia, Canada, and found that their assessment added insights beyond those provided by existing policy analyses. Ban et al (2015b) used a SES lens to examine changes in governance through time in the Great Barrier Reef Marine Park, Australia, assessing changes in property rights and multiple goods and ecosystems services.…”
Section: Summary Of the Articlesmentioning
confidence: 99%
“…These tended to be descriptive case studies. Those studies that took a more analytical approach all used the design principles to assess the effectiveness of management in their case studies (Lacroix and Richards 2015, Lancaster et al 2015, Villamayor-Tomas et al 2016. Drafts of several articles initially attempted to do both, i.e., use the SES framework and design principles, but ended up focusing on design principles only.…”
Section: Observations and Challengesmentioning
confidence: 99%
See 1 more Smart Citation
“…They can be used to assess the potential of a given institutional design to lead to successful self-governance; however, they cannot explain variation in management success in common pool resource institutions that come about from different real-world contexts (the rules-in-use) of similarly designed common pool resource institutions. The design principles were intended for community-scale resources management and are therefore appropriate for this study, but it should be noted that modifications to the principles for larger-scale common pool resource management have been suggested by Lacroix and Richards (2015). Data on the design and implementation of JFM by GIZ were collected through participatory observation and document review (project documents, progress reports, monitoring reports).…”
Section: Design Principles: Institutional Analysis Of Joint Forestry mentioning
confidence: 99%
“…The design principles originally emerged from studies examining community-based systems (i.e., where communities organize themselves to manage their resources), but their relevance to larger systems is an area of active study. For example, the design principles have been scaled up for large systems like the Great Barrier Reef Marine Park, the International Convention for the Conservation of Atlantic Tuna, and the BC Carbon Tax (Epstein et al 2014, Lacroix andRichards 2015).…”
Section: Introductionmentioning
confidence: 99%